Comparison of Laparoscopic Sleeve Gastrectomy and Intragastric Balloon Procedures - Fatih Türkoğlu; Serdar Yormaz (Gazi Medical Journal)
Objective: We aimed to compare laparoscopic sleeve gastrectomy (LSG), which is proven to be effective for obesity, with intragastric balloon procedure (IGB), a minimally invasive technique. Methods: The study included patients admitted to our surgical clinic between December 2018 and October 2021. During the study period, 106 patients with morbid obesity treated at our clinic were analyzed. The results of 65 patients who underwent LSG and 41 who underwent IGB were retrospectively evaluated. Demographic characteristics, body mass index, and comorbidities were recorded. Furthermore, the quality of life questionnaires that the participants completed before the treatment procedures and one year after the treatment were analyzed. p<0.05 value was considered statistically significant. Results: The mean age of the patients was 42.97 years. The mean preoperative body weight and BMI value were 122.75±11.03 kg and 43.98±4.19 kg/m2, respectively, for the LSG patients, while they were 122.75±11.03 kg and 43.98±4.19 kg/m2, respectively, for the IGB patients. The mean length of hospital stay was 3.31±0.80 days in LSG and 1.12±0.40 days in IGB, and the mean operation time was 63.92±7.07 minutes in LSG and 21.66±4.39 minutes in IGB. Both results were statistically significant (p<0.05). There was no mortality, and one patient who underwent IGB experienced intolerance. Conclusion: Both LSG and IGB procedures being performed today are effective methods for obesity treatment. However, LSG is more effective in improving obesity-related comorbidities and weight loss, whereas IGB is a safe method that is more easily applicable, reversible, and has lower complication rates.